Uses and misuses of the fudge factor in quantitative discovery proteomics. Issue 14 (21st July 2016) - Giai Gianetto, Quentin; Couté, Yohann; Bruley, Christophe; Burger, Thomas
Abstract : Selecting proteins with significant differential abundance is the cornerstone of many relative quantitative proteomics experiments. To do so, a trade‐off between p ‐value thresholding and fold‐change thresholding can be performed because of a specific parameter, named fudge factor, and classically noted s 0 . We have observed that this fudge factor is routinely turned away from its original (and statistically valid) use, leading to important distortion in the distribution of p ‐values, jeopardizing the protein differential analysis, as well as the subsequent biological conclusion. In this article, we provide a comprehensive viewpoint on this issue, as well as some guidelines to circumvent it.